INTEGRASI RASIO DAN RUHANI DALAM ISLAM: IMPLEMENTASINYA DALAM PENDIDIKAN KARAKTER GENERASI Z - Sholihah, Lukluk Alawiyatush; Sholihah, Tsaniyatus; Esha, Muhammad In'am; Rossidy, Imron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education in the contemporary era faces an integrative crisis that separates the rational-philosophical dimension from the spiritual-Sufi dimension. This separation becomes even more acute when dealing with Z Generation, which has grown up in a digital ecosystem: cognitively intelligent yet often spiritually empty, experiencing existential anxiety, and losing a sense of life’s meaning. This study aims to formulate an integrative framework between Islamic philosophy and Sufism as the foundation for Z Generation character education, as well as its implementation through the stages of tazkiyatun nafs. This study employs a qualitative approach using library research, with data analyzed descriptively and analytically through a philosophical lens. Research findings indicate that Islamic philosophy and Sufism were never intended to exist separately; both are grounded in the belief that truth originates from God and can be attained through both reason and the heart. The integration of reason and spirituality gives rise to three core competencies: metaphysical awareness, inner resilience (sabr), and a transcendent orientation. Its implementation in character education for Z Generation is realized through the three stages of tazkiyatun nafs: takhalli (purifying the soul of undesirable traits through epistemological ijtihad and self-reflection), tahalli (adornment of the self with virtuous traits through logical discourse and the cultivation of worship), and tajalli (the radiant manifestation of divine consciousness through an understanding of tawhid and the station of tawakkal). This integration offers a model of character education that not only fosters intellectually intelligent individuals but also spiritually mature and morally resilient individuals in the digital age.